0.6(5x+15)=2.7-(x+3)

Simple and best practice solution for 0.6(5x+15)=2.7-(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.6(5x+15)=2.7-(x+3) equation:


Simplifying
0.6(5x + 15) = 2.7 + -1(x + 3)

Reorder the terms:
0.6(15 + 5x) = 2.7 + -1(x + 3)
(15 * 0.6 + 5x * 0.6) = 2.7 + -1(x + 3)
(9 + 3x) = 2.7 + -1(x + 3)

Reorder the terms:
9 + 3x = 2.7 + -1(3 + x)
9 + 3x = 2.7 + (3 * -1 + x * -1)
9 + 3x = 2.7 + (-3 + -1x)

Combine like terms: 2.7 + -3 = -0.3
9 + 3x = -0.3 + -1x

Solving
9 + 3x = -0.3 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
9 + 3x + x = -0.3 + -1x + x

Combine like terms: 3x + x = 4x
9 + 4x = -0.3 + -1x + x

Combine like terms: -1x + x = 0
9 + 4x = -0.3 + 0
9 + 4x = -0.3

Add '-9' to each side of the equation.
9 + -9 + 4x = -0.3 + -9

Combine like terms: 9 + -9 = 0
0 + 4x = -0.3 + -9
4x = -0.3 + -9

Combine like terms: -0.3 + -9 = -9.3
4x = -9.3

Divide each side by '4'.
x = -2.325

Simplifying
x = -2.325

See similar equations:

| 9y-14y=-22-28 | | 5y+1=4y+10 | | 80+10p=150+5p | | 11x=47+8 | | 7s^2+5s-1=0 | | 2(3m-5)+6= | | 15c^2-2c-8=0 | | 15y-60y=0 | | 3p+9=2p+14 | | 36x+4y=22 | | 3c^2=22c+16 | | x-8=-2x-1 | | y+0.4=0.8(y+2) | | 4m^2+5m=7 | | 5+(-12t)+8t= | | 7.7x+3.9y=-50 | | 0=7n-6-n^2 | | 9+4r-7= | | W^2-168=0 | | 5x^2+18x=0 | | 4y^2-15y=-11y-4 | | x^2+2*x+4=0 | | 2(x-3)-4=3(x-5)-2 | | (4y^2)-15y=-11y-4 | | 4x-6(2x-1)=2 | | -16-6.5= | | 6n^2-18-18=6 | | r+0.12=0.20 | | -4.9=-5.7+x | | m+4=-6.7 | | 4.11x=16 | | 3c+12-c=78 |

Equations solver categories